2016
DOI: 10.1371/journal.pone.0156705
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Different Cervical Screening Strategies in Islamic Republic of Iran: A Middle-Income Country with a Low Incidence Rate of Cervical Cancer

Abstract: ObjectiveInvasive cervical cancer (ICC) is the fourth most common cancer among women worldwide. Cervical screening programs have reduced the incidence and mortality rates of ICC. We studied the cost-effectiveness of different cervical screening strategies in the Islamic Republic of Iran, a Muslim country with a low incidence rate of ICC.MethodsWe constructed an 11-state Markov model, in which the parameters included regression and progression probabilities, test characteristics, costs, and utilities; these wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…As known, HPV DNA test along with routine Pap smear could reduce colposcopy rate in ASCUS patients [5]. A report recommended an organized cervical screening with HPV DNA testing for women in Iran, beginning at age 35 and repeated every 10 or 5 years [6]. However, biomarkers are required to select patients for colposcopy screening in low and middle income countries where DNA and cytology testing are too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…As known, HPV DNA test along with routine Pap smear could reduce colposcopy rate in ASCUS patients [5]. A report recommended an organized cervical screening with HPV DNA testing for women in Iran, beginning at age 35 and repeated every 10 or 5 years [6]. However, biomarkers are required to select patients for colposcopy screening in low and middle income countries where DNA and cytology testing are too expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Khodakarami et al recommended starting the cervical cancer screening at the age of 30 with a repetition of every five years and continuing until the age of 69 [ 54 ]. The results of a study showed that the most cost-effective screening method is screening with HPV that begins at the age of 35 and is repeated every 10 years [ 55 ]. Nokiani et al conducted a study to determine the cost-effectiveness of Pap smear in Kermanshah.…”
Section: Resultsmentioning
confidence: 99%
“…Ennek érdekében célszerű, ha több információ áll rendelkezésre a kulcsszereplők elvárásairól, preferenciáiról, értékítéleteiről. Mobinizadeh et al [2016] [Nahvijou et al, 2016], a testsúlycsökkentés műtéti beavatkozással nem járó (non-invasive) lehetőségei [Nojomi et al, 2016], a haemophilus influanzae type B elleni immunizáció költséghatékonysága [Moradi-Lakeh-Shakerian-Esteghamati, 2012], konzerváló és helyreállító fogászat hatékonysága és költséghatékonysága [Mobinizadeh et al, 2014]. A szerzők a teljes találati listát nem közölték.…”
Section: Egészségügyi Technológiaelemzés Iránbanunclassified